2021
DOI: 10.1177/23259671211056645
|View full text |Cite
|
Sign up to set email alerts
|

Health Conditions, Substance Use, Physical Activity, and Quality of Life in Current and Former Baseball Players

Abstract: Background: A comprehensive understanding of lifestyle (health conditions and substance use), health-related quality of life (HRQoL), flourishing (holistic representation of health), and physical activity can inform stakeholders (players, coaches, and clinicians) and help improve long-term health across the life span. Purpose: To describe health conditions (comorbidities or diagnoses), substance use, physical activity, HRQoL, and flourishing in current and former collegiate and professional baseball players an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Pitchers were first given a questionnaire to complete upon arriving at the lab. The questionnaire was adopted by the research team from a cricket health and well-being study 25 and was piloted and refined for use on baseball personnel including a group of current and former baseball players (n = 121), collegiate and professional baseball coaches (n = 5), and medical professionals (sport physician, physical therapists, and athletic trainers; n = 4) who specialize in treating baseball players. 26 The degree of to which an athlete was specialized was defined in conjunction with current published guidelines and categorized as low-, moderate-, or high-level specialization based upon the athlete's answer to three survey questions (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Pitchers were first given a questionnaire to complete upon arriving at the lab. The questionnaire was adopted by the research team from a cricket health and well-being study 25 and was piloted and refined for use on baseball personnel including a group of current and former baseball players (n = 121), collegiate and professional baseball coaches (n = 5), and medical professionals (sport physician, physical therapists, and athletic trainers; n = 4) who specialize in treating baseball players. 26 The degree of to which an athlete was specialized was defined in conjunction with current published guidelines and categorized as low-, moderate-, or high-level specialization based upon the athlete's answer to three survey questions (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Athletes consider it more acceptable to see a psychologist for performance or goal-setting reasons than seeking help for depression ( Gulliver et al, 2014 ). These issues continue to manifest when untreated, resulting in many athletes engaging in unhealthy coping mechanisms, such as substance abuse and overtraining ( Wolanin et al, 2015 ); substance abuse has shown to persist, and even worsen post-retirement ( Kerr et al, 2014a ; Bullock et al, 2021 ).…”
Section: Research Strategymentioning
confidence: 99%
“…sports and regions demonstrate specific behaviors, for example, chewing tobacco in American baseball [11] and snus by Scandinavian athletes [12,13]. Inhalation of heated tobacco (i.e.…”
mentioning
confidence: 99%